Global Economic Prospects, January 2014 : Coping with Policy Normalization in High-Income Countries - World Bank (Washington, DC, 2014)
High-income economies appear to be finally turning the corner, contributing to a projected acceleration in global growth from 2.4 percent in 2013 to 3.2 percent this year, 3.4 percent in 2015, and 3.5 percent in 2016. Overall, growth in developing countries is projected to pick up modestly from 4.8 percent in 2013 to 5.3 percent this year, 5.5 percent in 2015, and 5.7 percent in 2016. In the baseline, the withdrawal of quantitative easing (and its effect on the long end of U.S. interest rates) is assumed to follow a relatively slow orderly trajectory. If, however, the taper is met with an abrupt market adjustment, capital inflows could weaken sharply—placing renewed stress on vulnerable developing economies. In a scenario where long-term interest rates rise rapidly by 100 basis points, capital inflows could decline by as much as 50 percent for several quarters.